Inverted Responses of the Carbon Cycle to Orbital Forcing in Mesozoic Periplatform Marginal Basins: Implications for Astrochronology. Issue 6 (9th June 2020) - Martinez, Mathieu; Guillois, Landry; Boulvais, Philippe; Deconinck, Jean‐François
Abstract: Astrochronology depends on the faithful record of insolation forcing in climatic proxies, including the carbon isotope composition measured on bulk carbonates (δ 13 Ccarb ). In marginal basins close to carbonate platforms, the source of carbonate is varied, which can impact the record of the astronomical cycles in the δ 13 Ccarb signal. We compare here the δ 13 Ccarb values together with detrital and weathering proxies before and during a crisis in the platform carbonate production (Weissert event, Valanginian, 135 Ma) to document how a change in the carbonate source can affect the record of the orbital forcing by the carbon isotope system. The level of burial diagenesis was insufficient to alter the clay mineral assemblages, which are linked to cyclic changes in weathering conditions. The δ 13 Ccarb values correspond to the values measured in other parts of the basin, which experienced various levels of burial diagenesis, suggesting that they also reflect a paleoenvironmental signal. In marl beds, the δ 13 Ccarb values increase with detrital and kaolinite content, suggesting that humid/arid cycles controlled the evolution of the δ 13 Ccarb signal in marl beds. Before the Weissert event, the δ 13 Ccarb values in the limestone beds increase with CaCO3 content and arid conditions. This can reflect the change of type of carbonate produced in shallow‐marine environments and exported to the basin. These environmental changes disrupted the record of the eccentricity cycles in the δ 13 Ccarb signal. The sources of carbonate must therefore be clearly identified and documented before using the δ 13 Ccarb series for orbital tuning in hemipelagic areas close to carbonate platforms. Plain Language Summary: The Milankovitch cycles are periodic motions of the Earth's orbit at the origin of cyclic climatic changes recorded in strata. Regular decimetric alternations between marl and limestone strata deposited in deep seas are notably caused by humid‐arid cycles orbitally induced, which usually take 20, 000 yr to be deposited. Counting these strata cycles allows the duration of the geological periods to be calculated. The so‐called astronomical timescales depend on the faithful stratal record of the Milankovitch cycles. Carbon isotopes are used to build astronomical timescales despite sources of carbon are varied and often unconstrained. We compare here proxies from the continental weathering and erosion to the marine carbonate production recorded in marl‐limestone alternations. We show here that the different sources of carbonates—produced by organisms with variated ecological needs—disrupt the record of the Milankovitch cycles in the carbon isotopes. The sources of carbon in sediments have to be compared to additional climatic proxies before being used for astronomical timescales. In addition, we propose models to explain how the Milankovitch cycles can be recorded and disrupted in the proxies studied here. Key Points: The δ 13 Ccarb measured in hemipelagic marl and limestone beds shows opposite responses to eccentricity depending on the source of carbonates A careful control of the source of carbonates should be done before using δ 13 Ccarb series for astronochronology in Mesozoic marginal basins Comparisons with the insolation models suggest that more carbonated intervals occurred at eccentricity maxima